2020
DOI: 10.1111/aen.12506
|View full text |Cite
|
Sign up to set email alerts
|

Coextinction of Pseudococcus markharveyi (Hemiptera: Pseudococcidae): a case study in the modern insect extinction crisis

Abstract: The majority of modern insect extinctions are likely unrecorded, despite increasing concern for this hyperdiverse group. This is because they are either yet to be discovered and described, their distributions and host associations are poorly known, or data are too sparse to detect declines in populations. Here, I outline the likely extinction of an Australian mealybug, Pseudococcus markharveyi Gullan 2013, which was discovered and described less than 15 years ago but was highlighted recently as one of five mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…2021; Hogendoorn et al . 2021; Moir 2021) report severe declines at the site and landscape scale within the last decade.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…2021; Hogendoorn et al . 2021; Moir 2021) report severe declines at the site and landscape scale within the last decade.…”
Section: Figmentioning
confidence: 99%
“…2021; Hogendoorn et al . 2021; Moir 2021), together with a very recently published 8 year study of the diet of the Australian hobby Falco longipennis during the Millennium Drought (Debus et al . 2020), have identified rapid declines in insect abundance in the immediate past at small spatial scales (site and landscape) (Fig.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys detected individuals at the only accessible location in the river catchment, confirming species persistence. In contrast, a post‐fire reconnaissance survey found that the only known population of the Banksia montana mealybug Pseudococcus markharveyi was extinguished in the 2019–2020 fires, and consequently, the species is now considered likely to be extinct (Moir, 2021).…”
Section: Reconnaissance Survey and Monitoring Objectivesmentioning
confidence: 99%